Improvement of the stability of the alcohol dehydrogenase from baker's yeast using polymers and salts for alcohol determination in beverages - Gattás, Edwil Aparecida de Lucca [UNESP]; Ribeiro, Maria Henrique Lourenço; Peres, Maristela de Freitas Sanches [UNESP] (My University, 2014)
An alcohol dehydrogenase (ADH) was purified from dry baker's yeast. This is a key enzyme of the primary short-chain alcohol metabolism in many organisms. In the present study, the obtained enzymatic preparation of baker's yeast, containing 2.7 U/mg of ADH, was used in the reactions. The purified extract of the ADH obtained from Fermix commercial dry yeast, presented the highest activity and purification factor when ammonium sulfate was added in the precipitation of protein, in the range 35-60% (w/v). The enzymatic preparation was maintained for 2 months in the lyophilized form at 4oC (retention of 96.2% of activity) in the presence of 1 mmol/L of sodium azide, and it maintained 47% of activity for 30 days at 30°C in the presence of 15% PEG. The assays of ethanol (detection range 5 mM -150 mM or 2.3 × 10-4 - 6.91 × 10-3 g/L) in different samples in alcoholic beverages, presented a maximum deviation of only 2.1%. Assays of recovery of the substrate (99.25%) added in the wine showed that the methodology is viable for this sample type. The standard curve and the analytic curve of this method meet the conditions of precision, sensitivity, simplicity, and low cost, required for a useable analytical method.
Keywords: Alcohol dehydrogenase; Alcoholic beverages; Baker's yeast; Ethanol determination; Purification; Stability